China's wind industry: Leading in deployment, lagging in innovation. (July 2017) - Lam, Long T.; Branstetter, Lee; Azevedo, Inês M.L.
Abstract: China's massive carbon emissions and air pollution concerns have led its government to embrace clean energy innovation as a means of transitioning to a more sustainable energy system. We address the question of whether China's wind industry has become an important source of clean energy technology innovation. We find that in terms of wind capacity expansion, China has delivered enormous progress, increasing its wind capacity from virtually no wind capacity in the early 2000s to 140 GW by 2015. However, in terms of innovation and cost competitiveness, the outcomes were more limited: Chinese wind turbine manufacturers have secured few international patents and achieved moderate learning rates compared to the global industry's historical learning rate. Leading China-based indigenous producers are likely to remain important global players for the foreseeable future, but further progress in reducing the cost of capital equipment may slow relative to the recent past. However, opportunities in lowering curtailment rates and improving turbine quality can reduce China's overall levelized cost of electricity for wind. Highlights: Analyze wind power patenting trends of Chinese inventors and firms. Many Chinese patents, though few were granted by foreign patent offices. Chinese international patents are less likely to be cited than foreign counterparts. China's wind industry managed to reduce production costs, but learning rate is low.